Pengaruh Organizational Citizenship Behavior (OCB) Terhadap Kinerja Karyawan di Grand Rocky Hotel Kota Bukittinggi - Muhammad Aulia Fadli; Hijriyantomi Suyuthie (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2022)
This research stems from the lack of optimal performance of employees at Grand Rocky Hotel Bukittinggi, and the presence of employees who feel reluctant to help other employees. The purpose of this research is to determine the effect of Organizational Citizenship Behavior (OCB) on employee performance, Grand Rocky Hotel Bukittinggi. This research is a type of quantitative research with a causal associative approach. The population in this research is 88 people. The sampling method used the Slovin formula and the sample in this research amounted to 75 people. Research information is obtained by distributing questionnaires or questionnaires compiled based on a grid of research variable indicators, with 5 answer options that have been tested for validity and reliability. Data analysis using simple linear regression analysis method. The results of the research explain that OCB has a positive and significant effect on employee performance where the partial significance test (t test) with a significance of 0.004 <0.05. Which means, in the Organizational Citizenship Behavior (OCB) hypothesis, H1 is accepted and H0 is rejected. concluded that OCB has a positive and significant effect on employee performance. In the calculation of the coefficient of determination (R2) of 0.106, which means that the independent variable (X) affects as much as 10.6% of the dependent variable (Y) and as much as 89.4% is influenced by other variables